A pilot school health service in southwestern Swaziland, 1961, 62, 63 - Laufer, Walter Ernst (Department of Public Health and Family Medicine, 2020)
Swaziland is a British Protectorate of approximately 6,700 square miles. It is a subtropical country, border in the East by Mozambique and in the North, West and South by the Transvaal. There are approximately 270,000 Africans and 10,000 persons of other races living in the Territory. The country is divided into Highveld, Middleveld and Lowveld regions. The work described here was carried out in the South Western highveld. This is mountainous terrain, with an approximate altitude of 3,500 feet and an annual rainfall of about 30". The terrain is a succession of mountains and valleys, with several perennial streams and rivers coursing through it. The climate is variable, with hot summers and cold winters, with rainfall predominantly in the summer. Large man made forests are scattered throughout the area, and there is some cutting and processing of timber, but industries as such are not found in that part of the Territory.